2015
DOI: 10.1007/s10461-015-0997-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Frequency of Heterosexual Anal Intercourse Among Young People: A Systematic Review and Meta-analysis

Abstract: Abstract:We aim to assess if heterosexual anal intercourse (AI) is commonly practiced and how frequently it is practiced by young people.We searched PubMed for articles published 1975 to July 2014 reporting data on the proportion of young people (mean age <25) practicing heterosexual AI (AI prevalence) and on number of AI acts (AI frequency). Stratified random-effects meta-analysis and meta-regression were used to produce summary estimates and assess the influence of participant and study characteristics on AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 148 publications
(45 reference statements)
6
35
0
Order By: Relevance
“…Although scarce, the available data on AI frequency suggests that AI is practised frequently, with 2.4-15.9% of all intercourse acts being anal among all FSW study participant samples. Similar to previous review findings regarding heterosexual AI practice among young people and South Africans [37,38], we found a non-statistically significant indication that AI prevalence may have increased over time. In qualitative research Indian and East African FSW have described AI practice during sex work as becoming more common over time due to increased client demand [9,[39][40][41].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although scarce, the available data on AI frequency suggests that AI is practised frequently, with 2.4-15.9% of all intercourse acts being anal among all FSW study participant samples. Similar to previous review findings regarding heterosexual AI practice among young people and South Africans [37,38], we found a non-statistically significant indication that AI prevalence may have increased over time. In qualitative research Indian and East African FSW have described AI practice during sex work as becoming more common over time due to increased client demand [9,[39][40][41].…”
Section: Discussionsupporting
confidence: 86%
“…AI is a highly stigmatised behaviour in many societies and thus its reporting is likely subject to social desirability bias and is likely more accurately reported using more confidential interview methods [37,38]. As the majority of studies in this review used FTFI, the least confidential interviewing method, our pooled estimates of AI prevalence and estimates of AI frequency likely underestimate its practice among FSW.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…AI prevalence did not increase with longer recall periods as would be expected if people do not practice AI all their life; instead, recall period had no discernible effect, which we also found in our systematic review on AI practice among young people [5]. These observations suggest that either reporting accuracy decreases over time, as previously reported in other sexual behaviour studies [8385], and/or that those who initiate AI continue to practice it all their life.…”
Section: Discussionsupporting
confidence: 63%
“…This is may be to be lower than for vaginal intercourse , although a systematic review of South Africa indicated equal or higher condom use during anal intercourse . Some studies suggest that heterosexual anal intercourse has become more common over time but, generally, trends in heterosexual anal intercourse in sub‐Saharan Africa are poorly understood and impacts of different types of sexual intercourse on population‐level sexual risks could not be evaluated in this study.…”
Section: Discussionmentioning
confidence: 89%